Targeted Therapy in Thyroid Cancer: State of the Art. Issue 5 (May 2017) - Valerio, L.; Pieruzzi, L.; Giani, C.; Agate, L.; Bottici, V.; Lorusso, L.; Cappagli, V.; Puleo, L.; Matrone, A.; Viola, D.; Romei, C.; Ciampi, R.; et al.
Abstract: Thyroid cancer typically has a good outcome following standard treatments, which include surgery, radioactive iodine ablation for differentiated tumours and treatment with thyrotropine hormone-suppressive levothyroxine. Thyroid cancers that persist or recur following these therapies have a poorer prognosis. Cytotoxic chemotherapy or external beam radiotherapy has a low efficacy in these patients. 'Target therapy' with tyrosine kinase inhibitors (TKIs) represent an important therapeutic option for the treatment of advanced cases of radioiodine refractory (RAI-R) differentiated thyroid cancer (DTC), medullary thyroid cancer (MTC) and possibly for cases of poorly differentiated (PDTC) and anaplastic thyroid cancer (ATC). In the last few years, several TKIs have been tested for the treatment of advanced, progressive and RAI-R thyroid cancers and some of them have been recently approved for use in clinical practice: sorafenib and lenvatinib for DTC and PDTC; vandetanib and cabozantinib for MTC. The objective of this overview is to present the current status of the treatment of advanced DTC, MTC, PDTC and ATC with the use of TKIs by describing the benefits and the limits of their use. A comprehensive analysis and description of the molecular basis of these drugs and the new therapeutic perspectives are also reported. Some practical suggestions are also given for the management to the potential side-effects of these drugs.